2016
DOI: 10.1177/0040517516629141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber length and blending method on the tensile properties of ring spun chitosan–cotton blend yarns

Abstract: Chitosan has been widely studied for use in many areas, such as for its applications in the biomedical, engineering and pharmaceutical fields, as well as in industry, because of its unique properties, including biodegradability, antimicrobial activity, polycationic nature and biocompatibility. Thanks to the rapid development of materials science, chitosan applications are now possible in textiles. However, there are still many limitations of chitosan fibers in terms of their high electrostaticity, poor mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 30 publications
(29 reference statements)
3
44
0
Order By: Relevance
“…In addition, the simulation results show that CS fibers will migrate outwards in CS–CT blended yarn due to a greater z -direction offset of CS fibers. The spinning experiments of Lam and colleagues 4 support this, in which Hamilton migration indices of CS fibers are positive (i.e., outward migration) for all CS–CT blended yarn. Compared with pure CS and pure CT, CS–CT blended yarn has increased strength due to the inward migration of CT fibers, and improved antibacterial properties due to the outward migration of CS fibers.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, the simulation results show that CS fibers will migrate outwards in CS–CT blended yarn due to a greater z -direction offset of CS fibers. The spinning experiments of Lam and colleagues 4 support this, in which Hamilton migration indices of CS fibers are positive (i.e., outward migration) for all CS–CT blended yarn. Compared with pure CS and pure CT, CS–CT blended yarn has increased strength due to the inward migration of CT fibers, and improved antibacterial properties due to the outward migration of CS fibers.…”
Section: Resultsmentioning
confidence: 78%
“…Due to both low strength and poor spinnability of CS, ring spinning, which contributes to higher yarn quality and is more flexible in application compared to other spinning systems, is used to produce CS–cotton blended yarn. 4 In the ring-spinning process, the drafted fiber strand leaves the front roller nip and is twisted into a yarn. This twist region between the front roller nip and the fiber convergence point is called the spinning triangle, which is a critical region.…”
mentioning
confidence: 99%
“…A series of yarn assessments was conducted. 16 The properties of the yarns are given in Table 2. Fourteen gauge knitted jersey fabrics samples of five different yarns were produced to test their physical properties for comfort.…”
Section: Methodsmentioning
confidence: 99%
“…With reference to some of the previous research and preliminary experiments conducted by our research team, through the modification of chitosan spinning technology to solve the spinning problem caused by yarn spinning of a high percentage of chitosan fibers. 16 Besides, chitosan based yarn fabric is proven to have positive advantages over traditional medical gauze, especially during the first stage of healing, and there is a linear relationship between the percentage composition of chitosan and performance. 17 Undoubtedly, there are more benefits of chitosan-based yarn fabric than nonwoven fabric in terms of the structure and capacity of the layered system, sustainability, and potential comfort.…”
mentioning
confidence: 99%
“…Therefore, the mechanical properties and biofunction of yarns must be carefully balanced to ensure sufficient strength and comfort handle and maintain stable biofunctions while controlling the production difficulty and costs. Studies [11][12][13] have shown that factors associated with the blending process, such as blending time (fibre or sliver blending) and spinning factors, may influence the distribution of yarn fibres. Regarding the ratios of biofunctional fibres, variables must be examined not only for academic purposes but also for industrial and domestic application.…”
Section: Chitosan Textile Productionmentioning
confidence: 99%